Activated mast cells in periprosthetic joint infection-associated tissue - Fisher, Cody R.; Patel, Robin (Frontiers in Immunology, 2023)
Background: Periprosthetic joint infection (PJI) is a devastating complication of total joint arthroplasty surgery. Increased densities of activated mast cells have been predicted to be present in PJI compared to non-infectious arthroplasty failure based on analysis of transcriptomic data, but their presence in PJI-associated periprosthetic tissues has not been visually confirmed. Objective: This preliminary study investigated the presence and activation status of mast cells in periprosthetic tissues associated with PJI. Methods: Periprosthetic tissues from five PJI cases as well as three arthroplasty failures due to instability and one due to stiffness, were immunohistochemically stained using tryptase and microscopically evaluated to enumerate mast cells and evaluate overall activation status within tissue samples. Mast cell activation was evidenced by release of tryptase into the extracellular space surrounding mast cells. Results: Mast cells were found in all samples, with average cellular densities of 22 and 26 cells/mm2 tissue in PJI and uninfected samples, respectively (p, 0.6610). Apparent mast cell activation and degranulation was readily observed throughout each of the five PJI samples studied, but not in any of the uninfected samples studied. Conclusions: While preliminary, these findings provide evidence for a role of mast cells in the immune response in PJI. Additional investigation of the role of mast cells during arthroplasty failure is warranted, providing a better understanding of underlying biology and informing potential diagnostic and treatment targets.